Differential approach in selecting beta-adrenoblocker therapy for patients with chronic heart failure and anaemia - T. M. Uskach; A. G. Kochetov; S. N. Tereschenko (Кардиоваскулярная терапия и профилактика, 2012)
Currently, beta-adrenoblockers (β-AB) are regarded as one of the major medication classes in the treatment of patients with chronic heart failure (CHF). In several international studies, β -AB therapy of CHF patients was associated with reduced levels of haemoglobin (Hb) and development of new anaemia cases. Anaemia is known as an adverse prognostic factor in CHF. Aim. To study the effects of β -AB therapy on the anaemia clinical course among CHF patients. Material and methods. The study included 90 ambulatory patients with Functional Class (FC) II-IV CHF and anaemia. The participants were divided into 3 equally sized groups (n=30 per group) and treated with carvedilol, metoprolol, or nebivolol for 6 months. Results. By the end of the follow-up, baseline Hb levels increased in the nebivolol group (p=0,028), and were also significantly higher than in the other two groups. In the carvedilol group, the levels of haematocrit (Ht) and glomerular filtration rate (GFR) significantly decreased (p=0,017 and 0,06, respectively). In the metoprolol group, no substantial changes of laboratory parameters were observed. The maximal reduction in baseline CHF FC was registered in the patients receiving nebivolol (p=0,037). A significant improvement in myocardial contractility, based on the echocardiography data, was registered in the carvedilol and nebivolol groups. Conclusion. Nebivolol therapy was associated with a significantly more pronounced reduction in pro-BNP levels, compared to carvedilol or metoprolol treatment (p<0,001). The nebivolol group also demonstrated the most pronounced improvement in quality of life of CHF patients (p<0,001). These findings suggest that nebivolol could be recommended as a medication of choice in patients with CHF and anaemia.